Development of control schemes for power converters and coordinated grid operation - Tang, Yi (2012)
Development of proper control schemes for three-phase pulse-width modulated (PWM) converters is crucial to achieve intended functions such as high conversion efficiency, low harmonic distortion and accurate control of real and reactive power flows. In this thesis, a complex-vector repetitive control scheme is first proposed for grid-connected inverters to achieve precise power flow control and also to reject harmonic disturbances induced from the grid and loads. Based on this control concept, a double-loop control scheme is then proposed for controlling power converters with output inductor-capacitor filters, and they can continuously supply critical and emergency loads during ac mains outage. In order to transfer electrical power into the grid more efficiently, an inductor-capacitor-inductor (LCL) filter is introduced and the accompanied stability issues are addressed. A systematic design of LCL-filter-based active power filter is presented to improve system power quality. To achieve harmonic free AC/DC power conversion, a one-cycle controlled active rectifier is proposed and its operation under non-ideal supply voltage conditions is also investigated. All the control algorithms and design methodologies presented in this thesis are verified by laboratory experimental results, which demonstrate their effectiveness and practicality.